An analytical study of the change in the area of ​​agricultural land in the Sheikh Saad district of Tartous Governorate (2013-2023) - ابراهيم طالب; جلال خضرة; محمود عليو (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study aims to analyze the decrease in the area of ​​agricultural land in the administrative units in the Sheikh Saad site and its surroundings spatially during the period (2013-2023), where a group of administrative units close to and relatively far from the city center, close to the public road and far from it, was chosen. The decrease was also linked to the area of ​​agricultural land due to urban expansion and the increase in population to determine the factors that contributed most to the decrease in the area of ​​agricultural land in the study area. The study relied on the use of the most important modern and accurate indicators to determine the rate of decrease in the area of ​​agricultural land, and one of these indicators is the index (NDVI).In addition, the index (NDBI) was used to define urban lands based on two Landsat8 satellite images taken in the dates 2013 and 2023. The study reached a set of results, the most important of which is: The area of ​​agricultural land at the level of the study area decreased from 3855.8 ha in 2013. to 3727.4 ha in 2023. The study showed a strong inverse relationship between urban growth and the area of ​​agricultural land, and a moderate inverse relationship between population growth and the area of ​​agricultural land. The study recommended the necessity of preserving agricultural lands and preventing horizontal urban sprawl towards them. It identified areas eligible for rapid urban growth and emphasized the necessity of monitoring them and preserving agricultural lands there.